Answer:
Already in standard form
Step-by-step explanation:
-4y=10
-4y= by
10= c
And in this case ax=0x, so it will not show up in the equation
0x-4y=10, which is already in standward form
Answer:
Step-by-step explanation:
T=16x+96 so if he wants to receive 130$ a day he must work at least 3 hours of over time.
Answer:
K=15
Step-by-step explanation:
Answer:
Step-by-step explanation:
In order to combine like terms, you have to isolate x and y from one side of the equation.
![\sf{-8z+\left(4.5\right)+3.5z+7y-1.5}](https://tex.z-dn.net/?f=%5Csf%7B-8z%2B%5Cleft%284.5%5Cright%29%2B3.5z%2B7y-1.5%7D)
<u>First, thing you do is remove parentheses.</u>
![\Longrightarrow: \sf{-8z+4.5+3.5z+7y-1.5}](https://tex.z-dn.net/?f=%5CLongrightarrow%3A%20%5Csf%7B-8z%2B4.5%2B3.5z%2B7y-1.5%7D)
<u>Solve.</u>
<u>Then, you combine like terms.</u>
![\Longrightarrow:\sf{-8z+3.5z+7y+4.5-1.5}](https://tex.z-dn.net/?f=%5CLongrightarrow%3A%5Csf%7B-8z%2B3.5z%2B7y%2B4.5-1.5%7D)
<u>Add/subtract the numbers from left to right.</u>
-8z+3.5z=-4.5z
<u>Rewrite the problem down.</u>
![\Longrightarrow: \sf{-4.5z+7y+4.5-1.5}](https://tex.z-dn.net/?f=%5CLongrightarrow%3A%20%5Csf%7B-4.5z%2B7y%2B4.5-1.5%7D)
<u>Solve.</u>
4.5-1.5=3
![\Longrightarrow: \boxed{\sf{7y+3-4.5z}}](https://tex.z-dn.net/?f=%5CLongrightarrow%3A%20%5Cboxed%7B%5Csf%7B7y%2B3-4.5z%7D%7D)
- <u>Therefore, the correct answer is 7y+3-4.5z.</u>
I hope this helps, let me know if you have any questions.